Consideration of Future Consequences Berdasarkan Pengalaman Melakukan Hubungan Seksual Pranikah pada Remaja Akhir - Khairatun Hisan; Kartika Sari (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2017)
Abstract: The purpose of this study is to determine consideration of future consequences from their experience in sexual intercourse before marriage in late adolescences. The samples included 90 subjects which are consisted 45 subjects who had sexual intercourse before marriage and 45 subjects who did not have sexual intercourse relations before marriage. The data are collected by using Consideration of Future Consequences Scale 14, which was developed by Joireman, Shaffer, Balliet, and Strathman (2012). The results of data analysis in this study using independent sample t-test showed that there are differences in consideration of future consequences in the late adolescences in terms of their experience in premarital sexual intercourse t (df) = -13.16 (88), p 0.05). It indicated that the late adolescences who had sexual intercourse before marriage have low CFC, whereas late adolescences who did not have sexual relations before marriage have higher CFC.Abstrak: Penelitian ini bertujuan untuk mengetahui consideration of future consequences berdasarkan pengalaman melakukan hubungan seksual pranikah pada remaja akhir. Penelitian ini melibatkan 90 subjek, yaitu 45 subjek melakukan hubungan seksual pranikah dan 45 subjek yang tidak melakukan hubungan seksual pranikah. Pengumpulan data menggunakan skala Consideration of Future Consequences Scale 14, yang dikembangkan oleh Joireman, Shaffer, Balliet, dan Strathman (2012). Hasil analisis data menggunakan independent sample t-test yang menunjukkan terdapat perbedaan consideration of future consequences pada remaja akhir ditinjau dari pengalaman melakukan hubungan seksual pranikaht (df) = -13,16 (88), p 0,05). Hal ini menunjukkan bahwa remaja akhir yang melakukan hubungan seksual pranikah memiliki CFC yang rendah sedangkan remaja akhir yang tidak melakukan hubungan seksual pranikah memiliki CFC yang tinggi.